El refugio guatemalteco en México. Análisis iconológico de las fotografías de Didier Bregnard: 1984-1985 - García Camacho, Gabriela (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
After a series of violent actions against its population with the purpose of remove every support from the Guatemalan guerrilla and which Efraín Ríos Mont in front of the dictatorship turned them into genocidal state policies, thousands of Guatemalans fled their country. From this large migration flow the Mexican government register that 24 000 Guatemalan people were welcomed in specialised camps located first in Chiapas and then in Campeche and Quintana Roo, where they received aid and protection from the Mexican Commission for help to the refugees (COMAR) and the United Nations High Commissioner for Refugees (UNHCR). As testimony of this project the book titled Refugiados guatemaltecos. Fotografías de Didier Bregnard was created. In it 123 photographs from the authorship of Didier Bregnard were published. This images are divided into three series where the experience of part of Guatemalan migrants inside the Mexican territory were captured. Hence, the purpose of our research is to analyse iconologically a selection of this pictures to decipher their significands, their intrinsic messages as well as the intentions of publicising the book.

Después de una serie de acciones de violencia en contra de su población con la finalidad de quitar todo apoyo a la guerrilla guatemalteca y que con Efraín Ríos Mont al frente del poder se convirtieron en políticas de Estado genocidas, miles de guatemaltecos huyeron de su país. De ellos se tiene en el registro oficial de México que 24 000 fueron acogidos en campamentos especializados, primero en Chiapas y después en Campeche y Quintana Roo, donde recibieron la asistencia y protección de la Comisión Mexicana de Ayuda a Refugiados (COMAR) y del Alto Comisionado de las Naciones Unidas para los Refugiados (ACNUR). Como testimonio de este proyecto se creó el libro titulado Refugiados guatemaltecos. Fotografías de Didier Bregnard. En él se publicaron 123 imágenes de la autoría de Didier Bregnard, divididas en tres series, que capturan la experiencia de parte de los migrantes guatemaltecos dentro del territorio mexicano. De esta manera el objetivo de nuestra investigación responde a analizar iconológicamente una selección de las fotografías y con ello, descifrar sus significados, el mensaje intrínseco; así como las intenciones de la mencionada publicación.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2021-0463; Historia de América; Migración; COMAR; Fotografía; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6468